Mineral and Bone Disease (MBD) on a Kidney Transplant Patient - Birne, R (2014)
A 50-year-old post-menopausal recipient of a kidney allograft with bone pain, osteoporosis, persistent hypercalcaemia and elevated parathormone (PTH) levels, despite a satisfactory graft function, was treated with bisphosphonates and cinacalcet starting, respectively, 5 and 6 months after renal transplantation (RT). Sixteen months after treatment, there was improvement of bone mineral density (BMD) measured by dualenergy X-ray absorptiometry (DEXA). A bone biopsy was taken, unveiling a surprising and worrisome result. Post-RT bone disease is different from classic CKD-MBD and should be managed distinctly, including, in some difficult cases, an invasive evaluation through the performance of a bone biopsy, as suggested in the KDIGO guidelines.